En bloc resection for primary spinal tumors with huge intrathoracic involvement: a surgical intervention for neurological decompression and oncological control - Liu, Fangzhi; Wang, Ben; Liu, Jiacheng; Liu, Xiaoguang; Wu, Fengliang; Zhou, Hua; Dang, Lei; Li, Yan; Tang, Yanchao; Liu, Xiao; Hu, Panpan; Li, Zihe; et al. (Frontiers in Neurology, 2025)
Study designRetrospective cross-sectional study.ObjectivesGiven the aggressive nature of primary spinal tumors, postsurgical local recurrence rates remain high. En bloc resection is currently the preferred treatment. However, the presence of a large thoracic cavity mass increases the surgical difficulty, risk, and likelihood of extensive complications. We report diagnostic and therapeutic characteristics, surgical strategies, and perioperative complications of such tumors treated with en bloc resection.MethodsWe reviewed 25 patients with primary spinal tumors and extensive thoracic cavity involvement who underwent en bloc resection at our center between 2012 and 2023 with a minimum postoperative follow-up of 1 year. We collected and analyzed data on surgical procedures, complication characteristics, and local tumor control and recurrence, and compared our findings with previous studies.ResultsWe included 25 patients (14 males and 11 females; mean age, 41.3 years). Of these, 14 patients underwent the first surgery, and 11 experienced recurrences. All patients underwent en bloc resection; 9 and 16 underwent intralesional and extralesional resections, respectively, 16 and 9 underwent posterior-only and combined approaches, respectively. The average surgery duration was 674 min, with an average estimated intraoperative blood loss of 2,388 mL. Eighty complications were recorded; 24 patients (96%) experienced at least one perioperative complication.ConclusionFor primary spinal tumors with huge thoracic cavity involvement, en bloc resection remains the optimal treatment for achieving local tumor control. Suitability for this procedure depends on the patient’s fitness for major surgery, the absence of distant metastases, and tumor resectability. Surgery can be performed via posterior-only or combined anteroposterior approaches.